Weight-Price Data as a Beef Cattle Management Tool - Fausett, Marvin R.; Dhuyvetter, Kevin C.; Lippert, George E. (My University, 1998)
This publication reports the prices of calves and yearlings by month in 25-pound weight increments, and shows how this information can be used for decision making.
MF2386_1998_11
Keywords: MF2386; Economics; Livestock; MF